THE EFFECT OF PROBLEM-BASED LEARNING IMPLEMENTATION ON STUDENTS’ PROBLEM-SOLVING ABILITY IN PROBABILITY TOPICS - Nely Salu Padang; Ruben Sonda (Almeera Education, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on students’ problem-solving skills in probability. This study uses a quantitative approach with an experimental method. The study population consists of students at STIE Jambatan Bulan who are enrolled in the Statistics course. The sample comprises 32 students divided into two groups: 16 students in the experimental group, who received instruction using the Problem-Based Learning model, and 16 students in the control group, who received conventional instruction. The research instrument consists of a problem-solving ability test on probability material. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the t-test at a 5% significance level. The results showed that the average problem-solving ability of students in the experimental class was 83.187, while the average problem-solving ability of students in the control class was 73.125. The results of the hypothesis testing showed that the calculated t-value (t-hitung) of 4.312 was greater than the critical t-value (t-table) of 1.697; therefore, H0 was rejected and H1 was accepted. Thus, the implementation of the Problem-Based Learning model has a positive effect on students’ problem-solving skills in probability. The Problem-Based Learning model has proven to be more effective than conventional teaching methods in improving students’ ability to understand, analyze, and solve problems related to probability concepts in statistics courses.